Produção de serapilheira e decomposição dos resíduos da colheita em povoamento de Eucalyptus no Espírito Santo - Moura, Roberto Rorras dos Santos (2016)
Efficient use of forest management techniques provides increased forest productivity and a sustainable ecosystem. Thus, knowledge of the litter production and its rate of decomposition is extremely important to be part of the nutrient cycling process, thus promoting better soil fertility. This study aimed to quantify the nutrient content of litter produced and evaluate its rate of decomposition, in a stand of Eucalyptus urophylla x Eucalyptus grandis, Aracruz, ES. For the sampling of litterfall and its decomposition were used six plots (30 x 30m), marked systematically in an area of 9.16 ha. Each plot contained five collectors 1m² distributed systematically being collected monthly litter deposited on them. Then this material was separated into fractions leaves / branches and miscellany. The contents, content and nutrient use efficiency. The rate of decomposition was performed by the weight loss method in nylon bags (litterbags). The treatments consisted of different fractions, with leaves, twigs, bark and waste combined (mixture of the three plant residues), which were distributed in each plot five litterbags each treatment. The collections of litterbags were performed at 30, 90, 180 and 365 days after installation of litterbags. After collecting the material, samples were sent to the laboratory to determine nutrient levels. Litter production had monthly variation in both studied fractions, with a total deposition of 4797.17 kg ha-1 yr-1, between 27 and 38 months old. The biomass fraction of leaves / miscellany corresponded on average 73%, which was also responsible for most of the return of nutrients through litterfall. The efficient use of macronutrients was evidenced in the following order P > S > Mg > K > Ca > N and the Mo micronutrients > Cu > Zn > B> Fe> Mn. The decomposition rate (k) of the plant residues was considered slow, and variations between 0.0010 and 0.0024 for the experimental treatments, indicating a time xi required 505-1087 days for the complete renewal of the litter. All levels of macronutrients were variations up to 180 days, with higher nutrient content in the fraction sheets for N, P, K and Mg, and the branches fraction Ca. Generally, the return of nutrients through the litter is significant in nutrient cycling processes by improving soil fertility with the decomposition of forest residues deposited.